Analisis Kemampuan Koneksi Matematis Siswa SMP Kelas VIII Pada Materi Sistem Persamaan Linear Dua Variabel - Riosanddy Narazetha; M Alviyan Mudzaqi; Nirwati Angela Al Ghani; Masta Hutajulu (Departement of Mathematics Education, 2019)
The purpose of this research is to analyze the ability of JUNIOR HIGH SCHOOL students ' mathematical connections in one school in Greenacres. The subject is grade VIII that add up to 34 people. Whereas the object of the research was the ability of mathematical connections students of class VIII. Data retrieval in this study using tests, i.e. tests essay material systems of Linear equations in two variables. Data analysis techniques used are descriptive statistical analysis. Data analysis of student learning math test results obtained that the ability of JUNIOR HIGH SCHOOL students ' mathematical connections subjected to one school in Cimahi still belongs to the very low percentage of 53.93%. Students who have the ability of mathematical connections with very high category only 4.9% of 34 students.The purpose of this research is to analyze the ability of JUNIOR HIGH SCHOOL students ' mathematical connections in one school in Greenacres. The subject is grade VIII that add up to 34 people. Whereas the object of the research was the ability of mathematical connections students of class VIII. Data retrieval in this study using tests, i.e. tests essay material systems of Linear equations in two variables. Data analysis techniques used are descriptive statistical analysis. Data analysis of student learning math test results obtained that the ability of JUNIOR HIGH SCHOOL students ' mathematical connections subjected to one school in Cimahi still belongs to the very low percentage of 53.93%. Students who have the ability of mathematical connections with very high category only 4.9% of 34 students.